Inequality and the global economic crisis - Dowd, Douglas Fitzgerald, 1919-; ebrary, Inc. (London ; New York : Pluto Press ; New York : Distributed in the United States of America exclusively by Palgrave Macmillan, 2009)
Inequality has always been with us. With the growth of capitalism across the globe, inequalities of income, wealth and power became increasingly extreme. Written by economist Douglas Dowd, this book shows that the present banking crisis is the result of the growth of inequality across the globe. The expansion of the financial sector has brought incredible riches to a select few, at the expense of the majority. Inequality was ignored, or described as a necessary aspect of a booming global economy. With the collapse of the world markets, the fallacy of this position is clear. Inequality and the Global Economic Crisis shows how it is only by addressing inequality that we can secure the health of our economies in the future.--Publisher.
Includes bibliographical references (p. 271-282) and index.
Electronic reproduction.
Keywords: Financial crises; Income distribution; Equality -- Economic aspects; Globalization -- Economic aspects; Capitalism; Poverty; Big business; Electronic books